El fetiche: un resplandor que ciega en la magna mujer de la publicidad - Campos Rodríguez, Vanessa Brasil (Pensar la Publicidad. Revista Internacional de Investigaciones Publicitarias, 2009)
In this paper it is analyzed the image of the new woman and her role in advertising. A series of seducing ads have been selected in which an omnipotent, phallic and menacing woman is presented. The products shown in the advisements are seen as an imaginary phallus, as a memory of the child’s most precious thing: the fetish. Therefore the role of women in these advertisements is to fulfill and ancient masculine desire in the imaginary and to outshine the real desire in the symbolic dimension.
Keywords: Fetish; Desire; Castration; Product; Advertisement; Image